1983
DOI: 10.1007/bf00735276
|View full text |Cite
|
Sign up to set email alerts
|

Responses of neurons of canine area postrema to neurotransmitters and peptides

Abstract: Captain "'Lomas E. Dayton (USAFSAM/RZV) was the Laboratory Project ScienZis-n-Cnarge.-When Government drawing: , pejecifications, or other data are used for any purpose other than in connection with a definitely Government-related procurement, tie United States Government incurs no responsibility or any obligation whatsoever. The fact that the Government may have formulated or in any way supplied the said drawings, specifications, or other data, is not to be regarded by implication, or otherwise in any manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…For example, systemic injection of cisplatin increases plasma levels of substance P and 5-HT (23,41), possibly derived from release of these factors from enteroendocrine cells of the gut. Direct application of 5-HT and substance P can activate neurons in the AP, and intracerebroventricular injection of cisplatin in the cat can produce emesis (11,67).…”
Section: Discussionmentioning
confidence: 99%
“…For example, systemic injection of cisplatin increases plasma levels of substance P and 5-HT (23,41), possibly derived from release of these factors from enteroendocrine cells of the gut. Direct application of 5-HT and substance P can activate neurons in the AP, and intracerebroventricular injection of cisplatin in the cat can produce emesis (11,67).…”
Section: Discussionmentioning
confidence: 99%
“…43 Other sources of 5-HT to the dorsal vagal complex region include the medullary raphe nuclei 136 and putative serotonergic cell bodies in the dorsal vagal complex such as the mNTS. 137 Not only are neurons within the AP region excited by 5-HT, 138 but postsynaptic serotonergic receptors (5-HT 1A , 5-HT 2A , 5-HT 3 , Figure 3. Biosynthesis of serotonin.…”
Section: Dorsal Vagal Complexmentioning
confidence: 99%
“…Neurons in the area postrema play an important role in the regulation of feeding behavior (Edwards and Ritter, 1981;Ritter and Edwards, 1984;South and Ritter, 1983). Previous studies have shown the chemosensitivity of area postrema neurons to several kinds of intestine peptide hormones that contribute to the feeding regulation, including CCK, which is known as a hunger suppressant (Carpenter et al, 1983;Funahashi and Adachi, 1993;Sun and Ferguson, 1997). It has been shown that systemic infusion of CCK induced cFos expression in the area postrema, indicates that it is a receptive site for circulating CCK (Luckman et al, 1993).…”
Section: Introductionmentioning
confidence: 96%